Peningkatan Motivasi dan Bimbingan Belajar Masa Pandemi Covid-19 bagi Anak Sekolah di RW 12 Kelurahan Serengan Kecamatan Serengan Kota Surakarta - Praptiningsih Praptiningsih; Eva Yuliyanti; Rachmawati Rachmawati; Qudsiyah Laili Rahmawati (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
This community service is motivated by the fact that several children are known to use mobile phone more often, play bicycles, play with their friends during study hours. In addition, there are several problems during online learning such as bored children, many school assignments, lack of understanding of school material, impatient parents and busy working parents, so there is no time to accompany their children when studying. Therefore, the activities to increase motivation and mentoring in learning aims to increase understanding, generating enthusiasm for learning, being responsible, being committed and having self-awareness of the learning importance. This community service method consisted of four stages, encompassing; observation, planning, implementation, and evaluation. These activities to increase motivation and tutoring has proven to be able to help children in RW 12, District Serengan by seeing the enthusiasm of the children in participating in tutoring activities, and self-awareness of the importance of learning so that school assignments can be completed properly, and improving the material during the activities of increasing motivation and tutoring